Rational Drug Use and Inventory Drug Management in the Peak of Covid-19 Pandemic in Indonesia - Didiek Hardiyanto Soegiantoro; Holy Rhema Soegiantoro; Gregory Hope Soegiantoro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
The rational use of drugs is characterized by the appropriate diagnosis, treatment, the appropriate drugs, dosage and duration, the appropriate information and counseling, and evaluation of treatment responses. Panic buying for medications used in the treatment of COVID-19, including prescribed drugs, resulted from public panic prompted by the high fatality rate of COVID-19. The demand for COVID-19 prescribed pharmaceuticals without a prescription refers to irrational drug use and uncontrollable growth in demand that has caused drug supply management issues. From June to August 2021, researchers conducted an observational study employing a cross-sectional analysis method from several pharmacies in each region. The findings revealed a more than 2-fold rise in demand for COVID-19 medications without a prescription, resulting in a more than 3-fold increase in purchasing lead times, as well as a more than 3-fold increase in drug purchase costs that could be regulated with government selling price standards. This study concludes that at the peak of the COVID-19 pandemic, there was an increase in irrational demand due to people's indiscipline to use rational drugs, resulting in drug scarcity and uncontrolled price increases.